Scientific Basis For The Development Of Meta-Competence In Primary School Teachers Based On Acmelogic Technology - Berdibekova F.A. (Periodica Journal, 2026)
This article examines the development of a competencybased approach in education today, the study of expanding competencies, and the consideration of cross-curricular metacompetence as a methodological approach to research activities, regardless of its scope
Keywords: competence; metacompetence; continuous self-education